Penyelesaian Sengketa Tumpang Tindih Sertifikat Hak Guna Bangunan dengan Hak Milik: Studi Kasus Tumpang Tindih Sertifikat Hak Guna Bangunan Nomor 00538/Nagara Lingkuang Aua - Hardian Feril (Jurnal Hukum Lex Generalis, 2025)
This research analyzes the overlapping case of HGB Certificate Number 00538/Lingkuang Aua under PT. PLN's name with 11 community property rights certificates in West Pasaman Regency. The overlap occurred due to manual administration systems in 1994, loss of PT. PLN's HGB documents, and land abandonment for 25 years. The community has physically occupied the land for residential purposes and obtained certificates through complete procedures. Consequently, both parties cannot conduct legal transactions on their land due to dispute status. The Land Office neglected to supervise abandoned land and failed to prevent overlapping certificate issuance. Mediation resolution failed, requiring settlement through Administrative Court to obtain binding legal certainty.